Political thought and political history : studies in memory of Elie Kedourie - Kedourie, Elie; Gammer, M.; Kostiner, Joseph; Shemesh, Moshe (Frank Cass, 2003)
This volume reveals the far-reaching range of Professor Kedourie's interests and the immense expanse of his horizons. The first part deals with philosophy, political thought and ideology and the second with history and politics.